Dharmagita as a Transformation of Hindu Culture in the 5.0 Era: Educational Perspective - Wiasti, Ni Komang; Wafa, Muhammad Sirril (Yayasan Keluarga Guru Mandiri, 2025)
Dharmagita is a sacred hymn in the Hindu's spiritual tradition. It conveys moral and cultural teachings. It also plays an essential role in both rituals and religious ceremonies. Maintaining Dharmagita in the era of Society 5.0 has faced a significant challenge. Additionally, rapid technological development has significantly influenced human lifestyle and communication. This is especially true for younger generations, who are more inclined to listen to modern music. This study aims to examine the transformation of Dharmagita as a medium of Hindu cultural expression in the digital era. Additionally, it plays a role in cultural preservation in education. The method used in this study is a qualitative approach. The researcher collects the data through interviews. The interview was conducted with some educators, religious leaders, and youths. It is also combined with participant observation and document analysis. The thematic analysis is used to interpret the data and display the insights into how Dharmagita adapts to digital platforms without losing its core values. The findings of the research show that educational initiatives, as well as digital innovation, are both main factors in maintaining Dharmagita. It becomes more engaging for younger audiences without losing its spiritual essence. This study contributes to the field of cultural education by highlighting how traditional religious expressions can evolve in the context of modern technology. In order to support the continuity of cultural and moral development.